Geostatistical Method Used in Quarry-Type Exploitation Based on Gaussian Simulation to Reduce the Uncertainty of Hydrogeological Values in Surface Mining in Peru - Serrano-Rojas, Rafael (2021)
El texto completo de este trabajo no está disponible en el Repositorio Académico UPC por restricciones de la casa editorial donde ha sido publicado.